Hubungan Pengetahuan, Sikap, Perilaku Pencegahan dan Kejadian Tuberkulosis Paru di Puskesmas Kedaton Bandarlampung - Ahmad Auli Revonadi; Dyah Wulan Sumekar Rengganis Wardani; Arif Yudho Prabowo; Retno Ariza Soeprihatini Soemarwoto (Journal of Health, Medical, and Psychological Studies, 2025)
Pulmonary tuberculosis (TB) is an infectious disease that remains a major public health problem in Indonesia. The transmission of pulmonary TB is influenced not only by biological factors but also by behavioral factors, particularly knowledge, attitudes, and preventive behaviors. Poor knowledge, unfavorable attitudes, and inadequate preventive behaviors may increase the risk of pulmonary TB transmission. This study aimed to determine the relationship between knowledge, attitudes, preventive behaviors, and the incidence of pulmonary TB in the working area of Kedaton Primary Health Center, Bandar Lampung. This study was an observational analytic study with a case–control design conducted from October to November 2025. A total of 202 respondents were included, consisting of 101 pulmonary TB cases and 101 non-TB controls, selected using a total sampling technique. Data were collected using a structured questionnaire and analyzed using univariate and bivariate analyses. The results showed a significant association between knowledge and the incidence of pulmonary TB (p = 0.010; OR = 2.214; 95% CI = 1.245–3.935) as well as between preventive behaviors and the incidence of pulmonary TB (p = 0.030; OR = 2.076; 95% CI = 1.114–3.867). Attitudes were not significantly associated with the incidence of pulmonary TB (p = 0.177; OR = 1.573; 95% CI = 0.869–2.846). Knowledge and preventive behaviors were associated with the incidence of pulmonary TB, whereas attitudes were not significantly associated.